Butanol production by immobilised Clostridium acetobutylicum in repeated batch, fed-batch, and continuous modes of fermentation - Dolejš, Igor; Krasňan, Vladimír; Stloukal, Radek; Rosenberg, Michal; Rebroš, Martin (Bioresource technology, 2014)
Clostridium acetobutylicum immobilised in polyvinylalcohol, lens-shaped hydrogel capsules (LentiKats(®)) was studied for production of butanol and other products of acetone-butanol-ethanol fermentation. After optimising the immobilisation protocol for anaerobic bacteria, continuous, repeated batch, and fed-batch fermentations in repeated batch mode were performed. Using glucose as a substrate, butanol productivity of 0.41 g/L/h and solvent productivity of 0.63 g/L/h were observed at a dilution rate of 0.05 h(-1) during continuous fermentation with a concentrated substrate (60 g/L). Through the process of repeated batch fermentation, the duration of fermentation was reduced from 27.8h (free-cell fermentation) to 3.3h (immobilised cells) with a solvent productivity of 0.77 g/L/h (butanol 0.57 g/L/h). The highest butanol and solvent productivities of 1.21 and 1.91 g/L/h were observed during fed-batch fermentation operated in repeated batch mode with yields of butanol (0.15 g/g) and solvents (0.24 g/g), respectively, produced per gram of glucose.
Keywords: Ethanol; aceton; Clostridium acetobutylicum; Cells, Immobilized; techniky vsádkové kultivace; Anaerobiosis; imobilizované buňky; Fermentation; anaerobióza; ethanol; butanoly; fermentace; Acetone; Batch Cell Culture Techniques; Butanols